Burden of care on family caregivers of patients of gastrointestinal cancers in a tertiary care institute - Sharma, Mohit; Devgun , Priyanka; Sharma, Ashwin (Indian Journal of Community Health, 2023)
Background: Gastrointestinal tract cancers are one of the leading causes of morbidity and mortality globally and cause family members to become primary caregivers. Method: The observational cross- sectional study was conducted using a pretested questionnaire and BSFC short form scale on 156 primary family care givers of patients suffering from and seeking treatment for cancer of the gastrointestinal tract from June 2021 to May 2022 in a tertiary care institute. Result: Mean age of family caregiver was 48.6 (4.7) years and the majority were female 111 (71.1 %). Average duration of primary care given was 2.62(1.24) years. 94 (60.2%) family care givers provided > 8hr duration of care. 103 (66%) of the family caregivers suffered from moderate burden, 39 (25%) from heavy burden and only 14 (8.97%) family caregivers considered burden as mild. Significant association was found between >8 hours of caregiving, caregiver having a comorbid illness, treatment outcome and financial distress borne during the course of treatment and burden of caregiving. Conclusion: Burden of caregiving in the family caregivers of cases of gastrointestinal cancer has the capacity to create ripples in the primary life domains of the caregiver and needs to be looked into.